Embriogenesis somatica en cultivares de cacao venezolanos - Velasquez Salazar, R.=700 1 Sandrea, Y.; Betancourt, C.; Mata, J.; Garcia, F.
(En, Es)
Ilus., 13 ref.
Keywords: THEOBROMA CACAO; EMBRIOGENESIS SOMATICA; CALLO; COTILEDONES; ESPAÑA